Presence of rare arterial arcade at 1st web space in the right hand and its possible clinical complications. - Anitha G,; Naveen K,; Srinivasa SR,; Snigdha M,; Satheesha NB, (Department of Surgery, UKM Medical Centre, 2013)
The thumb muscles require a rich blood supply due to extensive usage of the thumb to do daily chores. The thumb is solely supplied by the branches of the radial artery in most of the individuals. However, there are occasions where it is also supplied by the branches of the palmar arches of the hand which generally do not supply the lateral part of the hand. In the present case, the superficial palmar arch in addition to its normal branches, gave origin to a common trunk which traversed towards the web space between the pollex and the index finger. As it approached the base of the pollex, it divided into arteria radialis indicis and an arteria princeps pollicis. The arteria radialis indicis supplied the lateral side of index finger while, the arteria princeps pollicis further divided into a palmar branch and a dorsal branch. The palmar branch supplied the medial side of the pollex and the dorsal branch communicated with the 1st dorsal metacarpal artery, thus forming an arterial arcade at the base of the pollex. Proper understanding of the common arterial variations in the palmar arterial arches would be fundamental to the success of repair procedures in patients with hand trauma, particularly in plastic surgeries or during arteriografting.